Law of copyright and neighbouring rights: national and international perspectives - Ahuja, V. K. (New Delhi, 2007)
The book incorporates these changes adequately and provides inputs regarding Indian law and international law on the subject. It is unique in itself as it discusses all the multilateral conventions on copyright, irrespective of the fact whether India is a party to any particular treaty.
Keywords: Copyright law